Applicability of Islamic Education Philosophy to Educational Level Units from an Islamic Studies Perspective - Muhammad Rizqi Pratama; Zukhrufa Akbar Ramadan; Imroatus Solichah; Siti Ayu Nur Wanda Sari; Salsabila Nur Jannah; Latif Syaipudin (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2023)
This research aims to discuss the application of Islamic educational philosophy in developing education at the Islamic education unit level. The formulation of the problem in this research is how is the application of philosophy in building learning concepts, curriculum and actualizing students' self-development? This research method uses a literature study approach, with descriptive data analysis techniques. The results of this research explain that Islamic educational philosophy basically continues to encourage in-depth development of educational concepts in general. First, especially in the realm of learning concepts, learning also involves the process of organizing information, forming concepts and developing skills. With technological developments, learning is also increasingly integrated with digital tools and resources, opening up new opportunities in delivering learning material. Second, curriculum management in Islamic educational philosophy also emphasizes the importance of a student-centered learning approach. Teachers must understand the needs and potential of individual students to be able to help them develop holistically, both academically and morally. Third, self-actualization and development based on Islamic educational philosophy, is important to create an environment that supports individual spiritual and moral growth. This environment involves families, communities, and educational institutions that encourage individuals to live lives in accordance with Islamic principles.